Construction of Haris And Fatia vs Luhut Binsar Pandjaitan News Coverage By Kumparan and Tribunnews: (Framing Analysis on Kumparan and Tribunnews March-April 2022 Period) - Irfan Kurniawan; Abdul Malik; Media Sucahya (LONTAR: Jurnal Ilmu Komunikasi, 2022)
In the period from March to April 2022, Kumparan and Tribunnews presented news regarding thefeud between Haris and Fatia and Luhut Binsar Pandjaitan, regarding the issue of the miningbusiness in Intan Jaya Jaya, Papua. In their dispute, Haris and Fathia alleged that Luhut wasinvolved in the business, while Luhut said that the accusation was baseless and considered it a formof defamation. This study aims to find out how Kumparan and Tribunnews carry out framing,construction, and how the two media take sides, both for Haris and Fatia and for Luhut BinsarPandjaitan. This study uses the Framing analysis method proposed by Zhongdan Pan and Gerald M.Kosicki. The results of the study show that Kumparan constructed the news by giving theimpression that Polda Metro Jaya was on Luhut Binsar Pandjaitan's side. Kumparan also constructs news reports with a tendency to side with Haris and Fatia's camp, which can be seen from the selection of sources, most of whom are in their camp. Meanwhile, Tribunnews tends to be balanced in reporting, as evidenced by the selection and use of statements from sources that are balanced without taking sides with one side.